Pernikahan Dini Dalam Upaya Menjauhi Zina: Solusi atau Kontroversi? - Suprima, Suprima (Fakultas Syariah INSURI Ponorogo, 2022)
Nowadays, early age-marriage mostly happen in Indonesia because of married by accident, demands of customs, parents, and others. Indonesia is the 2nd country in Asia with the highest rate of early marriage and 37th in the world in 2007 (According to the United Nations Development Economic and Social Affairs (UNDESA) in 2010). In this study, researchers have more interest in exploring the phenomenon of early marriage that is rife by focusing on studying and knowing about early marriage as a solution or controversy to avoid an act of adultery. According to the view of Islam, customary law, and other laws. This study uses descriptive quantitative methods with data collection using a questionnaire. Although Islam does not determine the age for marriage, there are many factors that cause a negative impact if early marriage is not carried out with a good preparation. This thing will affect the psychological, physiological, social, economic, and other factors that lead to disadvantage. Therefore, it is better to prepared marriage more maturely before making a decision, because marriage in Islam is a worship and sacred thing.